Pandemic testimonies: Epistemic injustice from the Costa Rican school experience - Jiménez Asenjo, Wendy (2025)
To analyze the distance education processes developed during the 2020 school year in Costa Rica, the approaches of epistemic injustice were applied to the testimonies of families, students, and teaching staff. It is concluded that structural inequalities andadministrative verticality are evidence of epistemic injustice.